Feasibility of a dedicated e-learning platform in Modibbo Adama University of Technology, Yola School of Management and Information Technology, Department of Library and Information Science - Joshua, Dauda (2012)
The need for the e-learning platform system has been accentuated by both faculty and students of the Modibbo Adama University of Technology, Yola School of Management and Information Technology, Department of Library and Information Science (MAUTECH DLIS) to facilitate easy, reliable and extendable learning activities of the department. For this reason, this research aimed to survey the feasibility of mounting a dedicated platform to facilitate a distance learning program of MAUTECH DLIS in LIS courses. Hence, data were gathered from faculty and students, especially undergraduates, through a survey. There were three research instrument used: (1) survey questionnaire for students (undergraduates), (2) survey questionnaire for faculty members, (3) an exclusive interview session with the HOD, DLIS.